2018
DOI: 10.1093/humrep/dey290
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-3 mediates ovarian steroid hormone-induced motility of endometrial epithelial cells

Abstract: STUDY QUESTIONHow does aquaporin-3 (AQP3) affect endometrial receptivity?SUMMARY ANSWERAQP3, which is regulated by the combination and estrogen (E2) and progesterone (P4), induces epithelial–mesenchymal transition (EMT) of endometrial epithelial cells.WHAT IS KNOWN ALREADYEmbryo implantation is an extremely complex process, and endometrial receptivity is essential for successful embryo implantation. Estrogen and progesterone regulate endometrial receptivity. AQP3, which is regulated by estrogen (E2), increases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Endometrial cancer arises from tissue lining the uterus (the endometrium) and accounts for about 95% of uterine cancers. Protein and RNA for AQPs 1, 2, 3, 5, 7 and 9 are normally expressed in endometrium, in which the AQPs are thought to be involved in fluid exchange and estrogen-mediated regulatory effects [ 200 , 201 , 202 , 203 , 204 , 205 , 206 ]. AQP1 expression in endometrial cancer has been correlated with histologic grade, extent of myometrial invasion and the likelihood of extrauterine metastasis [ 207 ], but the functional role of AQP1 in this tissue remains to be defined.…”
Section: Resultsmentioning
confidence: 99%
“…Endometrial cancer arises from tissue lining the uterus (the endometrium) and accounts for about 95% of uterine cancers. Protein and RNA for AQPs 1, 2, 3, 5, 7 and 9 are normally expressed in endometrium, in which the AQPs are thought to be involved in fluid exchange and estrogen-mediated regulatory effects [ 200 , 201 , 202 , 203 , 204 , 205 , 206 ]. AQP1 expression in endometrial cancer has been correlated with histologic grade, extent of myometrial invasion and the likelihood of extrauterine metastasis [ 207 ], but the functional role of AQP1 in this tissue remains to be defined.…”
Section: Resultsmentioning
confidence: 99%
“…The expression levels AQP3 and AQP4 were upregulated in Ishikawa cells after the co-culture but not in HEC-1-A. Increased expression of AQP3 has been associated with both epithelial cell migration and endometrial receptivity [53], Genes in the intersection PBK PIM1, PLK1, PLK2, PSRC1, PTTG1, RASSF2, RASSF4, SPC24, SPC25, TACC3, TRIP13, TTK, TUBB4A, TUBG2, TXNIP, USH1C, VRK1 Sterol biosynthetic process 50 7 0.04 FDFT1, FDPS, HMGCS1, IDI1, INSIG1, MSMO1, while deficiency of AQP4 leads to female subfertility in mice [54]. Other genes upregulated in Ishikawa cells upon trophoblast challenge were desmin (DES), adrenomedullin (ADM), and intermidin (ADM2).…”
Section: Substrate Response To Embryo Attachmentmentioning
confidence: 90%
“…Epithelial-mesenchymal transformation (EMT) has been shown to be involved in the opening of the epithelial layer (Uchida et al, 2012;Owusu-Akyaw et al, 2019). Our previous studies have shown that P4 can mediate ezrin remodeling and cytoskeletal rearrangement through aquaporin-3, affecting epithelial cell motility and participating in EMT (Cui et al, 2018). And the movement of epithelial cells is inevitably dependent on the supply of energy, which indirectly indicates that the regulation of P4 on cells is involved in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%